Seasonal variabilities of low-latitude mesospheric winds - R. Rajaram; R. Rajaram; S. Gurubaran (Annales Geophysicae, 1998)
Observations of mesospheric winds over a period of four years with the partial reflection radar at Tirunelveli (8.7°N, 77.8°E), India, are presented in this study. The emphasis is on describing seasonal variabilities in mean zonal and meridional winds in the altitude region 70–98 km. The meridional winds exhibit overall transequatorial flow associated with differential heating in the Northern and Southern Hemispheres. At lower altitudes (70–80 km) the mean zonal winds reveal easterly flow during summer and westerly flow during winter, as expected from a circulation driven by solar forcing. In the higher altitude regime (80–98 km) and at all altitudes during equinox periods, the mean zonal flow is subjected to the semi-annual oscillation (SAO). The interannual variability detected in the occurrence of SAO over Tirunelveli has also been observed in the data sets obtained from the recent UARS satellite mission. Harmonic analysis results over a period of two years indicate the presence of long-period oscillations in the mean zonal wind at specific harmonic periods near 240, 150 and 120 days. Results presented in this study are discussed in the context of current understanding of equatorial wave propagation. Key words. Meteorological and atmospheric dynamics · General circulation · Middle atmosphere dynamics · waves and tides.